MicroRNA Biogenesis Machinery Is Dysregulated in the Endometrium of Infertile Women Suggesting a Role in Receptivity and Infertility. (August 2019) - Loke, Hannah; Rainczuk, Kate; Dimitriadis, Evdokia
MicroRNAs (miRs) regulate endometrial function and their dysregulation could underlie unexplained infertility in women. Ribonucleases including DICER and DROSHA, and the proteins, ARGONAUTE 1 (AGO 1) and 2 (AGO 2) regulate the biogenesis/maturation of miRs. We aimed to elucidate the expression and localization of miR biogenesis machinery components during the human menstrual cycle and compare their levels in endometrium from women with normal fertility and primary unexplained infertility. miR biogenesis components were measured by quantitative-RT-PCR and immunohistochemistry. In the endometrium of women with normal fertility, DROSHA immunolocalized maximally to the epithelium during the early and mid-secretory phases compared with the proliferative and late-secretory phases. Stromal DICER immunostaining intensity was higher in the late-secretory phase compared with all other phases in fertile women. DROSHA mRNA was reduced in the mid-secretory-infertile whole endometrial tissue (has all cells of the tissue), and primary epithelial and stromal cells while no differences were found in DICER, AGO1, and AGO2 mRNA. In the luminal epithelium, DROSHA staining intensity was reduced in early and mid-secretory-infertile while DICER staining was reduced in the early secretory-infertile compared with their respective fertile groups. DICER and DROSHA were dynamically regulated across the menstrual cycle and reduced levels during receptivity phase could underlie implantation failure/infertility.